2017
DOI: 10.1093/ije/dyx088
|View full text |Cite
|
Sign up to set email alerts
|

Focus on an unusual rise in pancreatic cancer incidence in France

Abstract: Pancreatic cancer incidence and mortality exhibited diverging trends. Incidence increased over the last 30 years in France whereas mortality did not vary in men and moderately increased in women. Incidence remained lower than mortality up to 2002. One cannot exclude the possibility that a similar trend may appear in other countries. Etiological studies are required to further explain this increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 19 publications
(30 reference statements)
1
27
0
Order By: Relevance
“…Indeed, two studies from Europe published in 2017 showed an increasing incidence trend in pancreatic cancer, and the study from France 23 also described diverging trends in pancreatic cancer incidence and mortality. 22 , 23 The incidence in both males and females increased during the past three decades, while mortality remained similar in men and slightly increased in women. 23 Several commentaries considered that these trends might be artificial.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, two studies from Europe published in 2017 showed an increasing incidence trend in pancreatic cancer, and the study from France 23 also described diverging trends in pancreatic cancer incidence and mortality. 22 , 23 The incidence in both males and females increased during the past three decades, while mortality remained similar in men and slightly increased in women. 23 Several commentaries considered that these trends might be artificial.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of pancreatic cancer (PC) has increased globally in the past decades. 1 , 2 , 3 About 55,440 new cases of PC are estimated in the USA in 2018, including 29,200 new cases in males and 26,240 female patients. 4 As a highly fatal malignance, PC has the lowest survival of human cancers; the 5-year relative survival rate only reaches 8%.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the various birth cohorts (i.e. from 1920 to 1950), the probability of developing a pancreatic cancer before age 75 has increased [ 4 ]. The standard rate of mortality has of course increased in parallel, especially in women [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…from 1920 to 1950), the probability of developing a pancreatic cancer before age 75 has increased [ 4 ]. The standard rate of mortality has of course increased in parallel, especially in women [ 4 ]. These findings are alarming; a further increase in the incidence of pancreatic cancer is expected over the next 15 years in France regardless of age or gender.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation